2021
DOI: 10.1186/s12913-021-06974-4
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of people seen in an acute hospital setting by a liaison mental health service: responses from an online survey

Abstract: Background In recent years the UK has expanded the provision of liaison mental health services (LMHS). Little work has been undertaken to explore first-hand experiences of them. Aims The aim of this study was to gain insights into the experiences of users of LMHS in both emergency departments and acute inpatient wards in the UK. Methods This cross-sectional internet survey was initially advertised from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Although there is no evidence that services that are not part of PLAN have poorer standards than PLAN members, PLAN membership suggests a willingness to undergo scrutiny by an external independent body and a desire to act upon suggestions for improvement. Given the variability of service user experience found from both from the current study and the online survey 3 , PLAN membership should be recommended for all LMHS in England.…”
Section: Stigmamentioning
confidence: 97%
See 1 more Smart Citation
“…Although there is no evidence that services that are not part of PLAN have poorer standards than PLAN members, PLAN membership suggests a willingness to undergo scrutiny by an external independent body and a desire to act upon suggestions for improvement. Given the variability of service user experience found from both from the current study and the online survey 3 , PLAN membership should be recommended for all LMHS in England.…”
Section: Stigmamentioning
confidence: 97%
“…There are relatively few studies of people's experiences of liaison mental health services (LMHS) in the UK. A recent internet survey of respondents' experiences of LMHS in England showed that only 31% of service users found their contact with such services helpful 3 . Latent class analysis identi ed three types of experience; those who had a positive experience, those who reported a negative experience and those who were non-committal.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the primary diagnosis of 'mental health disorder' is often used as a generic term to complete the triage process. This has often seen a patient streamed into a trajectory of care that may not reflect their current need, expectation, or presenting symptom (Guthrie et al 2021;Noblett et al 2015). Too often this label is used to describe any presenting situation that does not fit within a medical paradigm including, drug and alcohol, domestic violence and behaviourally disturbed patients (Oliver et al 2019).…”
Section: Impact Of Change Implementation and Challenges Remainingmentioning
confidence: 99%
“…This has often seen a patient streamed into a trajectory of care that may not reflect their current need, expectation, or presenting symptom (Guthrie et al . 2021; Noblett et al . 2015).…”
Section: Impact Of Change Implementation and Challenges Remainingmentioning
confidence: 99%
“…This is having a detrimental effect on the experiences and safety of patients seen in the acute hospital setting. A recent cross-sectional survey based in the UK reported that only 29% of patients felt comfortable during assessments and just 31% found liaison psychiatry contact helpful (Guthrie 2021).…”
Section: Clinical Reflectionmentioning
confidence: 99%